(untitled) (Bangladesh Journal of Agricultural Research, 2026)
A Vr-Wr graphical approach and genetic component analysis study for diallel analysis was carried out on snake gourd for fruit yield, yield attributes along with fruit quality traits at the farm of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Bangladesh during March to June 2019. Griffing half-diallel fashion involving seven parents viz., P1 (TC 01), P2 (TC 05), P3 (TC 24), P4 (TC 33), P5 (TC 02), P6 (TC 46) and P7 (TC 53) were effected to evolve 21 hybrids in snake gourd. The Vr-Wr graphical analysis demonstrated that over dominant gene action mainly responsible for early flowering and higher yield, partial dominant gene action accounted for number of fruits/ plant and complete dominance gene action responsible for fruit flesh thickness and number of seeds/ fruit. Estimates of genetic components such as D, H1 and H2 on traits revealed that the predominance of additive components over dominance components was found for fruit length, while for other remaining characters the predominance of dominance effect over additive effects in their expression.. The value (H1/D)1/2 indicated that a partial dominance was observed for fruit length and number of fruits/ plant but over-dominance was observed in the heritance of other characters in the parents. The unequal distribution of positive and negative alleles were found for all the characters. Narrow sense heritability was moderately high in days to 1st male flowering but high in days to 1st female flowering and fruit length, while it was low for other characters, indicating major part of additive gene action was responsible for the 1st three characters. The selection potential for days to 1st male flower open, days to 1st female flower open and fruit length would be high but it would not be high for other traits; therefore, recurrent selection for these three characters in early generation and hybridization and selection-based breeding methods in advanced generations may be effective for improvement of these traits in snake gourd. Bangladesh J. Agril. Res. 47(4): 401-421, December 2022